Degradation of diisopropyl methylphosphonate in aqueous solutions by ultrasonic irradiation combined with oxidation process - Muslim Hasan Allawi; Riyadh Sadeq ALMukhtar; Shurooq Talib Al-Humairi; Ali Dawood Salman; Tatjána Juzsakova; Viktor Sebestyén; Igor Cretescu (Chemistry Journal of Moldova: General, Industrial and Ecological Chemistry, 2023)

(untitled)
The degradation of diisopropyl methylphosphonate (DIMP) in aqueous solutions was studied using ultrasound irradiation with a fixed frequency of 26.2 kHz, following the first-order kinetic model. The study's primary goal was to determine the influence of the following experimental parameters: the pH (at different values of 2, 7 and 10), the initial concentration of DIMP (at different concentrations: 7, 14, 30, 50, 80 mg/L), the processing time (at different periods: 15, 30, 45, 60, 80, 90 min), and the concentration of the additive CCl4 (at different concentrations: 0.002, 0.004, 0.006, 0.008 mg/L). A DIMP removal efficiency of 98% from aqueous solution was obtained at pH 10 and 0.008 mg/L CCl4, after an ultrasound irradiation time of 45 min, pointing out the influence of the above-mentioned experimental parameters on the DIMP degradation process.